2022
DOI: 10.1007/s12664-022-01292-x
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Pacific consensus on small intestinal bacterial overgrowth in gastrointestinal disorders: An initiative of the Indian Neurogastroenterology and Motility Association

Abstract: In the clinical setting, small intestinal bacterial overgrowth (SIBO) is a frequent, but under-diagnosed entity. SIBO is linked to various gastrointestinal (GI) and non-GI disorders with potentially significant morbidity. The optimal management of SIBO is undefined while there is a lack of published consensus guidelines. Against this background, under the auspices of the Indian Neurogastroenterology and Motility Association (INMA), formerly known as the Indian Motility and Functional Diseases Association (IMFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 193 publications
0
36
0
8
Order By: Relevance
“…1 and 2), symptom type, dietary practices and psychological issues. The stubbornness of refractory IBS may be explained by multi-dimensional pathophysiological mechanisms, including altered gut motility, intestinal barrier dysfunction, gut microbiota dysbiosis, including SIBO, gut immune dysfunction, visceral hypersensitivity, bile acid malabsorption, FODMAP sensitivity, psychological factors and altered gut-brain interactions [11,17,139,140]. Investigations directed to these pathophysiological mechanisms, based on the local availability, should be undertaken (Figs.…”
Section: Statement 23: Dietary Fodmap Restriction Is Useful In a Prop...mentioning
confidence: 99%
“…1 and 2), symptom type, dietary practices and psychological issues. The stubbornness of refractory IBS may be explained by multi-dimensional pathophysiological mechanisms, including altered gut motility, intestinal barrier dysfunction, gut microbiota dysbiosis, including SIBO, gut immune dysfunction, visceral hypersensitivity, bile acid malabsorption, FODMAP sensitivity, psychological factors and altered gut-brain interactions [11,17,139,140]. Investigations directed to these pathophysiological mechanisms, based on the local availability, should be undertaken (Figs.…”
Section: Statement 23: Dietary Fodmap Restriction Is Useful In a Prop...mentioning
confidence: 99%
“…A sterile technique is used, and the sample is rapidly transported to the laboratory for seeding appropriate media to yield more precise colony counts. Cultures with colony counts ≥10 3 are considered diagnostic of SIBO ( 1 , 3 ), but the normal ranges of colony counts vary greatly along the length of the gut, increasing in the more distal regions of the GI tract, and there remains some controversy about the exact colony counts that define SIBO ( 7 , 75 ).…”
Section: Methodsmentioning
confidence: 99%
“…This threshold is supported in a 16S ribosomal RNA gene sequencing–based study, which found that a culture-based cutoff of >10 3 cfu/mL correlated well with clinical symptoms, breath test results, and sequencing ( 6 ). Debate on the appropriate diagnostic threshold remains, for instance, the Asian-Pacific consensus guidelines support the use of both diagnostic thresholds ( 7 ). Variable sampling and processing techniques have been an additional limitation with the use of small bowel aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promises was to attract the submission of Indian consensus and even Asian consensus on important issues in digestive diseases. In the last five years, five important consensuses on different digestive diseases got published, of which two are Asian consensus [17][18][19][20][21][22]. These consensus documents are on common gastrointestinal diseases such as chronic constipation, dietary issues in inflammatory bowel disease, gastroesophageal reflux disease, Helicobacter pylori infection, portal hypertensive upper gastrointestinal bleeding and small intestinal bacterial overgrowth [17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…In the last five years, five important consensuses on different digestive diseases got published, of which two are Asian consensus [17][18][19][20][21][22]. These consensus documents are on common gastrointestinal diseases such as chronic constipation, dietary issues in inflammatory bowel disease, gastroesophageal reflux disease, Helicobacter pylori infection, portal hypertensive upper gastrointestinal bleeding and small intestinal bacterial overgrowth [17][18][19][20][21][22]. I would also like to thank the supporting societies such as the Indian Society of Gastroenterology and the Indian Neurogastroenterology and Motility Association (earlier named Indian Motility and Functional Diseases Association) for undertaking these important scientific activities.…”
mentioning
confidence: 99%